Cuban Migration Trends and Their Impact on Central America Region - Cortez Sosa, Charleene (2017)
In recent years, the migration of Cuban population has taken new directions; this is mainly due to the migration policy flexibility adopted by the Cuban government and other Latin America governments, such as Ecuador, Grenada, Trinidad and Tobago, Dominican Republic, and Haiti, among others, by issuing visas in favorable conditions for the population. Although there are varied reasons to migrate, this population has traditionally migrated motivated by the United States Cuban Adjustment Act which grants administrative advantages for regularization; no other country of the continent offers this privilege. Due to their political exile condition, whoever arrives to the United States will easily have access to legal mechanisms for migrant regularization. Although there has been great work on migration in general terms, little has been addressed on the Cuban migration in the Central American region; possibly this is due to the difficulty to find quantitative information in this regard. The article aims to facilitate the understanding of migration in a context of flexibility and establishment of new relations between the Caribbean and Central America.